Population recovery and demographically constrained growth of Bezoar goat (Capra aegagrus) and Asian mouflon (Ovis gmelinii) in the Leopard Range of Nakhchivan, Azerbaijan - Elmar Babaev; Ismail Mammadov; Parviz Fatullayev; Elshad Askerov; Konul Akhmedova; Dashgin Ganbarov; Samir Gyliyev (Acta Biologica Sibirica, 2025)
The population status of the bezoar goat (Capra aegagrus) and the Asian mouflon (Ovis gmelinii), the primary prey of the Persian leopard (Panthera pardus), was assessed within the leopard's range in the southeastern part of the Nakhchivan Autonomous Republic of Azerbaijan. Surveys conducted from 2021 to 2022 using the transect method revealed a positive population trend for both ungulate species compared to previous censuses. Estimated densities of bezoar goats varied from 5.4 to 16.6 individuals/km² across different study sites, while mouflon densities ranged from 1.2 to 5.4 individuals/km². The total populations were estimated at approximately 2,000–2,200 bezoar goats and 800–1,000 mouflons across Nakhchivan. However, the sex-age structure of both species was characterized by a relatively low proportion of juveniles and yearlings, suggesting slow population growth. This demographic pattern is likely influenced by forage availability rather than poaching, which has been virtually eliminated since a complete hunting ban was instituted in 2001. The recovery of these prey populations is a critical factor for the conservation of the leopard in this region.